Evaluation of random amplified polymorphic DNA (RAPD)-PCR as a method to differentiate species of the Lactobacillus acidophilus-group and to determine the taxonomic status of the type strain of Lactobacillus casei subsp. casei (ATCC 393) - Du Plessis, Erika Magarete (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.